Bisbenzylisoquinoline Alkaloids of Cissampelos Sympodialis With in Vitro Antiviral Activity Against Zika Virus - da Silva, Poliana Gomes; Fonseca, Aventino H.; Ribeiro, Malu P.; Silva, Taizia D.; Grael, Cristiane F. F.; Pena, Lindomar J.; Silva, Tania M. S.; Oliveira, Eduardo de Jesus (Frontiers in Pharmacology, 2021)
In search of new antiviral compounds against Zika virus we conducted a bioassay-guided fractionation of bisbenzyilisoquinoline alkaloids isolated from Cissampelos sympodialis (Menispermaceae), a medicinal plant species endemic to Brazil. Six subfractions were obtained from a tertiary alkaloidal fraction of the rhizomes (TAFrz) using preparative high-performance liquid chromatography. All the subfractions were tested against Zika virus-infected using Vero cells as the cellular model to evaluate cytotoxicity and antiviral effective concentrations. The results showed that three of the six TAFrz subfractions tested were active. The most active ones were the subfraction 6 (that consisted of a mixture of the alkaloids methylwarifteine and warifteine present as a mixture at a ratio of 8.8:1.2 respectively) and the subfraction 5, that was later identified as warifteine, the major tertiary alkaloid of this species. Warifteine was able to significantly reduce virus titer in Zika virus-infected Vero cells demonstrated a promising antiviral effect against Zika virus with an IC50 of 2.2 µg/mL and this effect was selective a selectivity index (selectivity index, SI=) of 68.3). Subfraction 6 had an IC50= 3.5 µg/mL and was more cytotoxic than pure warifteine, with SI=6.14. Fraction 5 and fraction 6 were more potent in decreasing the viral titer of Zika virus-infected Vero cells than 6-methylmercaptopurine riboside (IC50= 24.5 µg/mL and SI=11.9), a mercaptopurine riboside with ZIKV antiviral activity used as a positive control. The antiviral activity of the samples compared favorably with that of the Zika virus antiviral agent 6-methylmercaptopurine riboside (IC50= 24.5 µg/mL and SI=11.9). Our data demonstrate that alkaloids of the bisbenzylisoquinoline type may be explored as newThese results suggest that bisbenzylisoquinoline alkaloids may be potential antiviral agents or as an useful pharmacophore for investigating ZIKV antiviral activity.serve as prototypes for future development.